High-pressure CO2 assisted extraction as a tool to increase phenolic content of strawberry-tree (Arbutus unedo) extracts. (October 2018) - Alexandre, A.M.R.C.; Matias, A.; Duarte, C.M.M.; Bronze, M.R.
Highlights: Arbutus unedo are a good source of phenolic compounds. HPCDAE increases phenolic content of extracts. Main phenolic compounds are gallic and quinic acid derivatives. Antioxidant activity also increased with HPCDAE. Abstract: Arbutus unedo fruits, commonly known as strawberry-tree fruits, can be used as raw material for the development of bioactive ingredients, besides other traditional applications. In this work, a high-pressure CO2 Assisted Extraction process (HPCDAE) was investigated in order to find the best process conditions to obtain extracts with a higher phenolic content (TPC) and antioxidant activity. The process parameters studied were pressure (100, 175 and 250 bar), temperature (40 °C, 55 °C and 70 °C) and volume solid:liquid (S:L)/CO2 ratios (20, 50 and 80%) and the extracts recovered compared with the extract obtained with a S:L conventional extraction. Results show that when the highest pressure (250 bar) temperature (70 °C) and lowest S:L/CO2 ratio (20%) are used, HPCDAE increases 1.41 times TPC of the extracts, compared to conventional S-L extract. A significant increase in the extraction of galloyl hexoside and 5-O-galloylquinic acid were observed after HPCDAE application. The intensification of both compounds extraction may be related with the increase in the antioxidant activity of the extracts. The results from this study show that HPCDAE is a promising tool to intensify the extraction of bioactive compounds from strawberry tree fruits.